Design and Implementation of Automated Plant Watering System Using ARDUINO - Bhattacharyya, Debalina; Kaur, Koelgeet; Choudhury, Chayanika; Sarkar, Eshita (International Journal of Computer Sciences and Engineering, 2025)
People enjoy plants, their benefits and the feeling related to nurturing them. However, in this fast life, for most people, it becomes a challenge to keep them healthy and alive. To accommodate this, we have developed a model, which makes a plant more self-sufficient, watering itself from a water tank. In this paper it will describe the implementation of a sensor which detects the humidity of the soil (of a potted plant) and supplies water, if required. The proposed work is based on Arduino Uno where the ATmega328P microcontroller that controls the water supplies. Once the soil gets dry, the sensor senses the requirement of water in the soil and sends a signal to Arduino. Arduino then instructs the pump to water the soil till the desired humidity and the sensor is deactivated again. This model will enable the people to enjoy having plants without the challenges related to absent or forgetfulness.